A multisystem inflammatory syndrome in children associated with COVID-19 in a 11-years-old girl - Bjelica Milena (Serbian Medical Society, 2021)
Introduction. Multisystem inflammatory syndrome in children (MIS-C) is a post-viral, life-threatening, inflammatory state with multisystem involvement that typically manifests 3–4 weeks after SARS-CoV-2 infection. In this article, we present the first case of MIS-C at the Institute for Child and Youth Health Care of Vojvodina at the beginning of the COVID-19 pandemic. Case outline. A previously healthy 11-year-old girl got sick two days before admission to the hospital with a fever, headache, vomiting, abdominal pain, and fatigue. She was tested positive for COVID-19 by a nasopharyngeal PCR swab with positive IgM and IgG antibodies. In the further course, the illness presented with prolonged fever, laboratory evidence of inflammation, multiorgan involvement such as respiratory, gastrointestinal, cardiovascular, and dermatologic. Based on CDC and WHO criteria, the diagnosis of MIS-C was made and IVIG and methylprednisolone were introduced with favorable clinical course. Conclusion. Every prolonged and unusual febrile state, especially if it is accompanied by gastrointestinal symptoms, in a school-age child, should be investigated in the direction of recent COVID-19 infection or exposure. In a case of a positive COVID-19 history or history of exposure, the MIS-C diagnosis should be considered.